Carbetocin: a therapy advance for prevention of postpartum haemorrhage - Bhalla, Amit (International Journal of Basic & Clinical Pharmacology, 2022)
Postpartum haemorrhage (PPH) is the major cause of maternal death. To prevent PPH, the routine administration of a uterus-contracting (‘uterotonic’) agent is a standard practice across the world. Oxytocin is the standard uterotonic agent recommended for this purpose, and is recommended for all women giving birth. Oxytocin is problematic as it requires cold storage and transport, and in low-resource settings, the cold chain is not commonly available. Heat-stable carbetocin is a promising alternative to oxytocin. Because of its heat stability, it can overcome the persistent problems with oxytocin quality as it does not require cold chain for storage and transport. Considering the totality of the evidence, it appears to have some additional desirable effects compared with oxytocin and a very favourable side effect profile similar to oxytocin. With a standardized dosing of single injection recommendation, it can address the variations in dosing regimen as is with oxytocin. Carbetocin has been added to the World Health Organization (WHO) essential medicines list of uterotonics for the prevention of excessive bleeding after childbirth, we might see a new standard of care in coming months for prevention of uterine atony.